Phytoseiid mites of the subtribe Amblyseiina (Acari: Phytoseiidae: Amblyseiini) from sub-Saharan Africa - Zannou, I.D.; Moraes, G.J. de; Ueckermann, E.A.; Oliveira, A.R.; Yaninek, John S.; Hanna, R. (2007)
This is the fifth publication in a series to determine the phytoseiid mites of sub-Saharan Africa. Thirty-one phytoseiid species of the subtribe Amblyseiina are reported in this paper. They refer to all species of this subtribe known to occur in sub-Saharan Africa. Ten of these species are described for the first time, 15 species are redescribed and 6 are not evaluated in this study. Most of those species were collected in cassava habitat in tropical Africa and in other habitats in South Africa. A key is included to help in the separation of these species.